Electrode and secondary battery including the same
By using graphene and a combined single-walled carbon nanotube structure conductive agent in the electrode active material layer of lithium secondary batteries, the problem of easy damage to the conductive network of lithium secondary batteries is solved, and the battery life characteristics are improved and Maintenance of electrical conductivity.
Patent Information
- Application Number
- CN202411391783.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-04
- Filing Date
- 2020-09-28
- Publication Date
- 2025-01-24
AI Technical Summary
During the charging and discharging process of existing lithium secondary batteries, the conductive network of single-wall carbon nanotubes is easily damaged, resulting in a decrease in battery life characteristics. The multi-wall carbon nanotubes are easily cut in the dispersion, which limits the conductivity of the electrodes. improve.
The carbon nanotimal structure that combines a single carbon nanot barrel unit including graphene and 2 to 5,000 single -wall carbon nanot barrels is used to form a longer carbon nanotone structure with 0.01 % to 0.5 % of the weight of 0.5 % to 0.5 % of the carbon nanotinal tube structure. The conductive network is to improve the life characteristics of the battery.
Effectively maintain the low resistance of the electrode, extend the life characteristics of the battery, and suppress the decline in conductivity during the charging and discharge process, significantly improved the input/output characteristics of the battery.
Smart Images

Figure CN119361696A_ABST
Abstract
Description
[0001] This application is a divisional application of an application with an application date of September 28, 2020, application number 202080041147.9, and invention name “Electrode and secondary battery comprising the electrode” (PCT / KR2020 / 013284, national phase entry date December 2, 2021).
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of Korean Patent Application No. 10-2019-0122965, filed on October 4, 2019, the disclosure of which is incorporated herein by reference. Technical Field
[0004] The present invention relates to an electrode including an electrode active material layer and a secondary battery including the electrode, wherein the electrode active material layer includes an electrode active material and a conductive agent, wherein the conductive agent includes graphene and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %. Background Art
[0005] With the development of technology and the recent increase in demand for mobile devices, the demand for batteries as energy sources has increased significantly, and various studies on batteries that can meet various needs have been carried out accordingly. In particular, as a power source for such devices, lithium secondary batteries with excellent life characteristics and cycle characteristics and high energy density have been actively studied.
[0006] A lithium secondary battery refers to a battery that includes a non-aqueous electrolyte containing lithium ions in an electrode assembly including a positive electrode, a negative electrode, and a microporous separator disposed between the positive electrode and the negative electrode, the positive electrode including a positive electrode active material capable of inserting / de-inserting lithium ions, and the negative electrode including a negative electrode active material capable of inserting / de-inserting lithium ions.
[0007] Since the conductivity of the electrode cannot be ensured only by the electrode active material, the resistance of the battery may be too high, and therefore, the electrode generally further includes a conductive agent. Generally, a point-type conductive agent such as carbon black is mainly used, and a linear conductive agent such as carbon nanotubes and carbon nanofibers has also been used to increase the battery capacity by further improving the conductivity.
[0008] Single-walled carbon nanotubes are one of the linear conductive agents, and because of their thin and elongated shape, the conductivity in the electrode active material layer is improved. Therefore, generally, a dispersion including single-walled carbon nanotube units is prepared, wherein the single-walled carbon nanotube units are completely dispersed so that the single-walled carbon nanotube units exist in a single-chain form, and then the dispersion is used to prepare an electrode slurry, and the electrode slurry is used to prepare an electrode active material layer. Therefore, the single-walled carbon nanotube exists in the electrode active material layer as a unit (single chain). However, when the battery is repeatedly charged and discharged, the surface of the single-walled carbon nanotube unit is damaged or the single-walled carbon nanotube unit is damaged, and therefore, it may be difficult to maintain a conductive network in the electrode active material layer. Therefore, the conductive network is blocked or reduced, and this reduces the life characteristics of the battery.
[0009] Therefore, there is also a method of using multi-walled carbon nanotubes, which can ensure conductivity even when the surface of the carbon nanotubes is damaged. However, in the case of multi-walled carbon nanotubes, since they are cut into too short a length due to the structure formed by the growth of nodes as units during the preparation of the dispersion, the improvement of the conductivity of the electrode is limited.
[0010] For planar conductive agents such as graphene, even if the conductivity is excellent, it is difficult to prepare a thin single layer of graphene, and in the case of using thick graphene, the battery efficiency is reduced. In addition, for planar conductive agents, the mobility of the electrolyte in the battery is limited due to the wide planar contact. In addition, since graphene mainly exists in the form of covering the surface of the electrode active material, it is not suitable for forming a long conductive network between the electrode active materials.
[0011] Therefore, a method is needed to reduce the resistance of the electrode and improve the life characteristics of the battery by introducing a new conductive agent. Summary of the invention
[0012] Technical issues
[0013] One aspect of the present invention provides an electrode having low resistance and capable of improving lifespan characteristics of a battery.
[0014] Another aspect of the present invention provides a secondary battery including the electrode.
[0015] Technical Solution
[0016] According to one aspect of the present invention, there is provided an electrode including an electrode active material layer, wherein the electrode active material layer includes an electrode active material and a conductive agent, wherein the conductive agent includes graphene and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.
[0017] According to another aspect of the present invention, a secondary battery including the electrode is provided.
[0018] Beneficial Effects
[0019] Since the electrode according to the present invention includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, a conductive network can be smoothly maintained even during the charge / discharge process of the battery. Therefore, the resistance of the electrode can be maintained at a low level, and the life characteristics of the battery can be improved. In addition, since the carbon nanotube structure exists in the electrode in the form of a long rope, even if the battery is continuously charged and discharged, the decrease in conductivity due to damage to the carbon nanotube structure can be suppressed, and a long conductive network can be formed. In addition, since the electrode includes graphene, the resistance of the battery can be further reduced due to the excellent conductivity of graphene. In addition, since graphene helps to form a short conductive network by covering the surface of the electrode active material, a conductive network can be uniformly formed on the entire electrode due to the combined use of graphene and carbon nanotube structures. In addition, since graphene exists while covering at least a portion of the carbon nanotube structure, a conductive network can be maintained even during repeated charging and discharging of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 1 is a scanning electron microscope (SEM) image of a multi-walled carbon nanotube unit (A) used in a comparative example of the present invention and a carbon nanotube structure (B, C) used in an example;
[0021] Figure 2 1 is a transmission electron microscope (TEM) image of a carbon nanotube structure (A) used in an example of the present invention and a single-walled carbon nanotube unit (B) used in a comparative example;
[0022] Figure 3 are SEM images and TEM images of graphene used in the embodiments of the present invention;
[0023] Figure 4 is a SEM image of the positive electrode of Example 1 of the present invention;
[0024] Figure 5 is a SEM image of the positive electrode of Example 1 of the present invention;
[0025] Figure 6 is a SEM image of the positive electrode of Comparative Example 4 of the present invention; and
[0026] Figure 7 This is a SEM image of the positive electrode of Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0027] It will be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it will be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best interpret the present invention, these words or terms should be interpreted as having meanings consistent with the technical concept of the present invention and the meanings in the context of related technologies.
[0028] The terms used in this specification are only used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise indicated, terms in the singular form may include plural forms.
[0029] It will be further understood that the terms “comprises,” “comprising,” or “having” in this specification specify the presence of stated features, numbers, steps, elements, or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or a combination thereof.
[0030] In the present specification, unless otherwise specifically stated, the expression "%" means % by weight.
[0031] In this specification, the expression "specific surface area" is measured by the BET (Brunauer-Emmett-Teller) method, wherein, specifically, the specific surface area can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mini II manufactured by Bell Japan.
[0032] The expression "average particle size (D 50 The average particle size D can be defined as the particle size at which the cumulative volume in the particle size distribution curve is 50%. For example, the average particle size D can be measured by using a laser diffraction method. 50 Laser diffraction can usually measure particle sizes from submicron to several millimeters, and can obtain results with high repeatability and high resolution.
[0033] In the present invention, the expression "single-walled carbon nanotube unit" means a tubular unit having a single wall composed of carbon atoms, and the expression "multi-walled carbon nanotube unit" means a tubular unit having multiple walls composed of carbon atoms.
[0034] The expression "graphene" in this specification refers to a carbonaceous structure having a form of stacking single or multiple graphite planes, being flexible, and having a thin film form.
[0035] Hereinafter, the present invention will be described in detail.
[0036] Electrode
[0037] The electrode according to the present invention includes an electrode active material layer, wherein the electrode active material layer includes an electrode active material and a conductive agent, wherein the conductive agent includes graphene and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure may be included in the electrode active material layer in an amount of 0.01 wt% to 0.5 wt%.
[0038] The electrode may include an electrode active material layer. The electrode may further include a current collector, and in this case, the electrode active material layer may be provided on one surface or both surfaces of the current collector.
[0039] The current collector is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, their alloys, these materials surface-treated with one of carbon, nickel, titanium, silver, etc., or calcined carbon can be used.
[0040] The current collector generally may have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to improve the adhesion of the electrode active material. In addition, the electrode current collector can be used in various shapes such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabric bodies, etc.
[0041] The electrode active material layer may include an electrode active material and a conductive agent.
[0042] The electrode active material may be a positive electrode active material or a negative electrode active material commonly used in the art, but its type is not particularly limited.
[0043] For example, as the positive electrode active material, a lithium oxide containing lithium and at least one metal such as cobalt, manganese, nickel, or aluminum can be used. Specifically, the lithium oxide may include: lithium manganese-based oxides (such as LiMnO2, LiMn2O, etc.); lithium cobalt-based oxides (such as LiCoO2, etc.); lithium nickel-based oxides (such as LiNiO2, etc.); lithium nickel manganese-based oxides (such as LiNi 1- Y1 Mn Y1 O2 (where 0 < Y1 < 1), LiMn 2-Z1 Ni z1 O4 (where 0 < Z1 < 2), etc.); lithium nickel cobalt-based oxides (such as LiNi1- Y2 Co Y2 O2 (where 0 < Y2 < 1) or analogs); lithium manganese cobalt-based oxides (such as LiCo 1-Y3 Mn Y3 O2 (where 0 < Y3 < 1), LiMn 2-Z2 Co z2 O4 (where 0 < Z2 < 2), etc.); lithium nickel cobalt manganese-based oxides (such as Li(Ni P1 Co Q1 Mn R1 )O2 (where 0 < P1 < 1, 0 < Q1 < 1, 0 < R1 < 1, and P1 + Q1 + R1 = 1) or Li(Ni P2 Co Q2 Mn R2 )O4 (where 0 < P2 < 2, 0 < Q2 < 2, 0 < R2 < 2, and P2 + Q2 + R2 = 2), etc.); or lithium nickel cobalt manganese-transition metal (M) oxides (such as Li(Ni P3 Co Q3 Mn R3 M 1 S )O2 (where M 1 is selected from the group consisting of aluminum (Al), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), tantalum (Ta), niobium (Nb), magnesium (Mg), boron (B), tungsten (W), and molybdenum (Mo), and P3, Q3, R3, and S are atomic fractions of each independent element, where 0 < P3 < 1, 0 < Q3 < 1, 0 < R3 < 1, 0 < S < 1, and P3 + Q3 + R3 + S = 1), etc.), and may include any one of them or a mixture of two or more.
[0044] The negative electrode active material may for example include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds that can alloy with lithium such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloy, Sn alloy, or Al alloy; metal oxides that may or may not be doped with lithium such as SiO v (0 < v < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composites including metal compounds and carbonaceous materials such as Si-C composites or Sn-C composites, and any one of them or a mixture of two or more may be used. In addition, a thin film of metallic lithium can be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbonaceous materials.
[0045] The electrode active material may be included in an amount of 70 wt % to 99.5 wt %, for example 80 wt % to 99 wt % based on the total weight of the electrode active material layer. When the amount of the electrode active material satisfies the above range, excellent energy density, electrode adhesion and conductivity may be achieved.
[0046] The conductive agent may include graphene and carbon nanotube structures.
[0047] (1) Graphene
[0048] Graphene is mainly disposed on the surface of the electrode active material to help form a conductive network between adjacent electrode active materials.
[0049] Graphene may include a structure in which 1 to 1,000 graphite planes are stacked, and specifically, the number of stacked graphite planes may be in the range of 1 to 500, for example, 1 to 100. When the number of stacked graphite planes satisfies the above range, high-quality graphene properties with flexibility can be utilized due to its small thickness, and graphene is easily and uniformly dispersed in the electrode active material layer. In addition, even with a small amount of graphene, the conductivity of the electrode active material layer can be significantly improved.
[0050] The average length of graphene can be 0.1 μm to 100 μm, particularly 0.1 μm to 10 μm, and more particularly 0.1 μm to 5 μm. When the average length meets the above range, graphene can exist while covering the electrode active material at an appropriate level. In addition, since graphene covers at least a portion of the carbon nanotube structure, the separation of the carbon nanotube structure and the electrode active material can be further suppressed. For this reason, the connection between the electrode active material and the electrode active material becomes tighter, and the conductivity can be further improved. In an electrode observed by a scanning electron microscope (SEM) or a transmission electron microscope (TEM), the average length corresponds to the average value of the length of the first 100 graphenes with a larger length and the length of the last 100 graphenes with a shorter length. Here, the expression "the length of graphene" means the longest length when it is assumed that there is a line from one point to another in a graphene sheet.
[0051] The average thickness of graphene can be 0.3nm to 300nm, particularly 1nm to 100nm, and more particularly 1nm to 50nm. When the average thickness meets the above range, graphene can better cover the electrode active material by utilizing the high-quality graphene characteristics that are flexible due to its small thickness, and graphene is easily and evenly dispersed in the electrode active material layer. In addition, even with a small amount of graphene, the conductivity of the electrode active material layer can also be significantly improved. In the electrode observed by SEM or TEM, the average thickness corresponds to the average value of the thickness of the first 100 graphenes with a larger thickness and the thickness of the latter 100 graphenes with a smaller thickness.
[0052] The BET (Brunauer-Emmett-Teller) specific surface area of graphene can be 100m 2 / g to 500m 2 / g, especially 100m 2 / g to 400m 2 / g, and more particularly 100m 2 / g to 300m 2 When the specific surface area satisfies the above range, the dispersibility of graphene in the electrode slurry is good, and even with a small amount of graphene, the conductivity of the electrode active material layer can be significantly improved. The BET specific surface area can be measured by the nitrogen adsorption BET method.
[0053] Graphene can be included in the electrode active material layer in an amount of 0.01 wt % to 1.0 wt %, particularly 0.05 wt % to 0.5 wt %, and more particularly 0.1 wt % to 0.5 wt %. When the amount of graphene satisfies the above range, the adhesion and conductivity of the electrode can be significantly improved by using only a small amount of graphene, and the input / output characteristics and life characteristics of the battery can be improved.
[0054] (2) Carbon nanotube structure
[0055] The carbon nanotube structure may include a plurality of single-walled carbon nanotube units. Specifically, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other. More specifically, in consideration of the durability and conductive network of the electrode, the carbon nanotube structure is most preferably a carbon nanotube structure in which 2 to 4,500, preferably 50 to 4,000, and more preferably 1,000 to 4,000 single-walled carbon nanotube units are bonded to each other.
[0056] The single-walled carbon nanotube units can be arranged side by side and combined in a carbon nanotube structure (having a flexible cylindrical structure in which the units are combined so that the long axes of the units are parallel to each other) to form a carbon nanotube structure. The carbon nanotube structure is connected to each other in the electrode to form a network structure.
[0057] Conventional electrodes including carbon nanotubes are usually prepared in the following manner: a conductive agent dispersion is prepared by dispersing bundle type or entangled type carbon nanotubes (in the form of single-walled carbon nanotube units or multi-walled carbon nanotube units attached or entangled to each other) in a dispersion medium, and then using the conductive agent dispersion. In this case, since the carbon nanotubes are completely dispersed in the conventional conductive agent dispersion, the carbon nanotubes exist as a conductive agent dispersion in which single-chain carbon nanotube units are dispersed. With respect to conventional conductive agent dispersions, since the carbon nanotube units are easily cut by excessive dispersion processes, the length of the carbon nanotube units is shorter than the initial length. In addition, the carbon nanotube units may also be easily cut during the rolling process of the electrode, and due to excessive changes in the volume of the electrode active material during battery operation, the carbon nanotube units (particularly single-walled carbon nanotube units) may be additionally cut or the surface is damaged. Therefore, due to the reduced conductivity of the electrode, the input / output characteristics and life characteristics of the battery are deteriorated. In addition, regarding the multi-walled carbon nanotube units, the structural defects are high due to the node growth mechanism (these units are not smooth and linear, but have nodes due to defects generated during the growth process). Therefore, the multi-walled carbon nanotube units are more easily cut during the dispersion process (see Figure 1 A), and the short-cut multi-walled carbon nanotube units can be easily aggregated by π-π stacking caused by the carbon surface bonding structure (sp2) of the unit. Therefore, it is more difficult to make the multi-walled carbon nanotube units more uniformly dispersed in the electrode slurry.
[0058] Alternatively, regarding the carbon nanotube structure included in the electrode of the present invention, since the carbon nanotube structure is a structure in which 2 to 5,000 single-walled carbon nanotube units maintaining relatively high crystallinity without structural defects are arranged side by side and bonded together (see Figure 1 B and C and Figure 2A) in the form of a rope, even if the volume of the electrode active material changes, the single-walled carbon nanotube unit will not be cut, and its length can be maintained smoothly, so that the conductivity of the electrode can be maintained even during the continuous charge / discharge process of the battery. In addition, since the high conductivity of the single-walled carbon nanotube unit with high crystallinity leads to an increase in the conductivity of the electrode, the input / output characteristics and life characteristics of the battery can be significantly improved. In addition, since the carbon nanotube structure is interconnected in the electrode and has a network structure, the excessive change in the volume of the electrode active material can be suppressed, thereby preventing the generation of cracks, and a strong conductive network can be ensured at the same time. In addition, even if cracks are generated in the electrode active material, the conductive network can be maintained because the carbon nanotube structure can connect the electrode active material while passing through the cracks. In addition, since the carbon nanotube structure is not easily damaged and can maintain its long shape, the conductive network can be enhanced over the entire electrode active material layer. In addition, by suppressing the peeling of the electrode active material, the electrode adhesion can be significantly improved.
[0059] In particular, from the perspective of using in combination with graphene, graphene is mainly arranged on the surface of the electrode active material to help ensure conductivity on a small length scale, but through the network structure and its larger length, the carbon nanotube structure can also help ensure conductivity on a large length scale. In addition, since graphene exists while covering at least a portion of the carbon nanotube structure, the conductive network can be tightly maintained even if the battery is repeatedly charged and discharged. Therefore, when graphene is used in combination with the carbon nanotube structure, since a tight and uniform conductive network can be formed on the entire electrode active material layer while reducing the total amount of the conductive agent, the input / output characteristics and life characteristics of the battery can be significantly improved.
[0060] In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit can be 0.5nm to 5nm, for example, 1nm to 5nm. When this average diameter is met, the conductivity of the electrode can reach the maximum even with a very small amount of conductive agent. When the prepared electrode is observed by TEM, the average diameter corresponds to the average value of the diameters of the first 100 single-walled carbon nanotube units with larger diameters and the last 100 single-walled carbon nanotube units with smaller diameters.
[0061] In the carbon nanotube structure, the average length of the single-walled carbon nanotube unit can be 1 μm to 100 μm, for example, 5 μm to 50 μm. When this average length is met, since a long conductive path for conductive connection between electrode active materials can be formed and a unique network structure can be formed, the conductivity of the electrode can be maximized even with a very small amount of conductive agent. When the prepared electrode is observed by TEM, the average length corresponds to the average of the lengths of the first 100 single-walled carbon nanotube units with a larger length and the last 100 single-walled carbon nanotube units with a smaller length.
[0062] The specific surface area of a single-walled carbon nanotube unit can be 500m 2 / g to 1,000m 2 / g, for example 600m 2 / g to 800m 2 / g. When the specific surface area satisfies the above range, since the conductive path in the electrode can be smoothly ensured by the wide specific surface area, the conductivity of the electrode can be maximized even with a very small amount of conductive agent. The specific surface area of the single-walled carbon nanotube unit can be specifically calculated by the nitrogen adsorption at liquid nitrogen temperature (77K) using Bell Japan's BELSORP-mini II.
[0063] The average diameter of the carbon nanotube structure can be 2nm to 200nm, particularly 5nm to 150nm, and more particularly 50nm to 120nm. When the average diameter meets the above range, since it effectively forms a conductive network structure and is conducive to connecting active materials, excellent conductivity can be achieved. When the prepared electrode is observed by SEM, the average diameter corresponds to the average value of the diameters of the first 100 carbon nanotube structures with larger diameters and the last 100 carbon nanotube structures with smaller diameters.
[0064] The average length of the carbon nanotube structure can be 1 μm to 500 μm, particularly 5 μm to 100 μm, and more particularly 10 μm to 70 μm. When the average length meets the above range, since it effectively forms a conductive network structure and is conducive to connecting electrode active materials, excellent conductivity can be achieved. When the prepared electrode is observed by SEM, the average length corresponds to the average value of the lengths of the first 100 carbon nanotube structures with a larger length and the last 100 carbon nanotube structures with a smaller length.
[0065] The carbon nanotube structure can be included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %, can be specifically included in an amount of 0.01 wt % to 0.15 wt %, and can be more specifically included in an amount of 0.01 wt % to 0.1 wt %. When the amount of the carbon nanotube structure meets the above range, since the conductive path in the electrode can be ensured, the life characteristics of the battery can be improved while the electrode resistance is kept at a low level. When preparing a conductive agent dispersion, the carbon nanotubes are fully dispersed (as a conventional dispersion method, in which the carbon nanotubes are dispersed so that the single-chain carbon nanotube units are separated from each other as much as possible), the carbon nanotube structure will not be generated, or even if the carbon nanotube structure is inadvertently generated, only a very small amount (e.g., 0.0005 wt %) of the carbon nanotube structure will be generated. That is, the above-mentioned amount range may never be reached in the usual way. Since the carbon nanotube structure is in a form in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and combined, even if the volume of the electrode active material changes, the carbon nanotube structure will not be cut and its length can be smoothly maintained. Therefore, due to the high conductivity of the carbon nanotube structure, the conductivity of the electrode can be maintained and the conductivity of the electrode can be smoothly ensured. Therefore, even if the amount of the carbon nanotube structure in the electrode is small, the input / output characteristics and life characteristics of the battery can be excellent.
[0066] In some cases, the single-walled carbon nanotube units can be surface treated by oxidation or nitridation to improve affinity with the dispersion.
[0067] The weight ratio of graphene to carbon nanotube structure may be in the range of 100:1 to 100:200, particularly 100:2 to 100:100, and more particularly 100:5 to 100:50. When the weight ratio satisfies the above range, the total amount of the conductive agent for an appropriate level of conductivity can be reduced while increasing the solid content of the electrode slurry. In addition, since the adhesion and conductivity of the electrode can be improved at the same time, the input / output characteristics and life characteristics of the battery can be significantly improved.
[0068] The electrode active material layer may further include a binder. The binder is used to ensure the adhesion between the electrode active materials and the adhesion of the electrode active material to the current collector, wherein the common binder used in the art can be used, and there is no particular restriction on its type. The binder may include, for example: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, carboxymethyl cellulose (carboxymethyl cellulose: CMC), styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one of them or a mixture of more than two thereof may be used.
[0069] The binder may be included in an amount of 10 wt % or less, for example 0.1 wt % to 5 wt % based on the total weight of the electrode active material layer. When the amount of the binder satisfies the above range, excellent electrode adhesion may be achieved while minimizing the increase in electrode resistance.
[0070] The electrode active material layer may further include at least one of polyvinylidene fluoride and hydrogenated nitrile rubber. Polyvinylidene fluoride and hydrogenated nitrile rubber play a role in helping to disperse bundle-type or entangled single-walled carbon nanotubes or bundle-type or entangled multi-walled carbon nanotubes in the conductive agent dispersion used in electrode preparation, and because the electrode slurry is prepared from the conductive agent dispersion, polyvinylidene fluoride and hydrogenated nitrile rubber may be included in the electrode.
[0071] Method for preparing electrode
[0072] Next, a method for producing the electrode of the present invention will be described.
[0073] The method for preparing an electrode of the present invention may include the following steps: preparing a graphene dispersion and a carbon nanotube structure dispersion (S1); and forming an electrode slurry including the graphene dispersion, the carbon nanotube structure dispersion and an electrode active material (S2).
[0074] (1) Preparation of graphene dispersion and carbon nanotube structure dispersion (S1)
[0075] 1) Preparation of graphene dispersion
[0076] After preparing a mixed solution including the graphene of the above-mentioned embodiment, a dispersion medium and a dispersant, a graphene dispersion can be prepared by using a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin mill, a TK mixer or a method of ultrasonic treatment. Since the dispersion medium and the dispersant can be the same as the dispersion medium and the dispersant used in the preparation of the carbon nanotube structure dispersion described later, the dispersion medium and the dispersant will be described below.
[0077] 2) Preparation of carbon nanotube structure dispersion
[0078] The preparation of the carbon nanotube structure dispersion may include the following steps: preparing a mixed solution including a dispersion medium, a dispersant, and bundle-type single-walled carbon nanotubes (bonded bodies or aggregates of single-walled carbon nanotube units) (S1-1); and dispersing the bundle-type single-walled carbon nanotubes by applying a shear force to the mixed solution, thereby forming a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded side by side (S1-2).
[0079] In step S1-1, a mixed solution can be prepared by adding bundled single-walled carbon nanotubes and a dispersant to a dispersion medium. The bundled single-walled carbon nanotubes exist in the form of bundles combining the above-mentioned single-walled carbon nanotube units, wherein the bundled carbon nanotubes generally include 2 or more, substantially 500 or more, for example, 5,000 or more single-walled carbon nanotube units.
[0080] The specific surface area of bundled single-walled carbon nanotubes can be 500m 2 / g to 1,000m 2 / g, for example 600m 2 / g to 800m 2 When the specific surface area satisfies the above range, since a conductive path in the electrode can be smoothly ensured by a wide specific surface area, the conductivity of the electrode can be maximized even with a very small amount of the conductive agent.
[0081] The bundled single-walled carbon nanotubes may be included in the mixed solution in an amount of 0.1 wt % to 1.0 wt %, for example, 0.2 wt % to 0.5 wt %. When the amount of the bundled single-walled carbon nanotubes satisfies the above range, since the bundled single-walled carbon nanotubes are dispersed at an appropriate level, a carbon nanotube structure may be formed at an appropriate level, and dispersion stability may be improved.
[0082] The dispersion medium may include, for example: an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); an alcohol such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; a glycol such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol. Alcohol; polyhydric alcohol, such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ether, such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; ketone, such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; ester, such as ethyl acetate, γ-butyrolactone and ε-propiolactone, and any one of them or a mixture of two or more thereof can be used, but the present invention is not limited thereto. Specifically, the dispersion medium can be N-methylpyrrolidone (NMP).
[0083] The dispersant may include at least one selected from hydrogenated nitrile rubber, polyvinylidene fluoride, and carboxymethyl cellulose, and specifically may be polyvinylidene fluoride or hydrogenated nitrile rubber.
[0084] In the conductive agent dispersion, the weight ratio of the bundle-type carbon nanotubes to the dispersant may be in the range of 1:0.1 to 1:7, for example, 1:1 to 1:6. When the weight ratio satisfies the above range, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, the carbon nanotube structure may be formed at an appropriate level, and the dispersion stability may be improved.
[0085] The solid content in the mixed solution can be in the range of 0.1 wt % to 20 wt %, for example, 1 wt % to 10 wt %. When the solid content satisfies the above range, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, the carbon nanotube structure can be formed at an appropriate level, and the dispersion stability can be improved. In addition, the electrode slurry can have a viscosity and elasticity suitable for the electrode preparation process, and it also helps to increase the solid content of the electrode slurry.
[0086] In step S1-2, the process of dispersing the bundle-type carbon nanotubes in the mixed solution can be performed by using a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin mill, a TK mixer, or an ultrasonic treatment (sonification) device. Among them, the beads mill method is preferred because this method can accurately control the diameter of the carbon nanotube structure, can achieve uniform distribution of the carbon nanotube structure, and can have cost advantages.
[0087] The bead milling method may be as follows: The mixed solution may be put into a container containing beads, and the container may be rotated to disperse the bundle-type single-walled carbon nanotubes.
[0088] In this case, the conditions for performing the bead milling method are as follows.
[0089] The average diameter of the beads may be 0.5 mm to 1.5 mm, for example 0.5 mm to 1.0 mm. When the average diameter satisfies the above range, the diameter of the carbon nanotube structure can be appropriately regulated without destroying the carbon nanotube structure during the dispersion process, and a dispersion solution with a uniform composition can be prepared.
[0090] The rotation speed of the container may be in the range of 500RPM to 10,000RPM, for example, 2,000RPM to 6,000RPM. When the rotation speed satisfies the above range, the diameter of the carbon nanotube structure can be properly regulated without destroying the carbon nanotube structure during the dispersion process, and a dispersion solution with a uniform composition can be prepared.
[0091] The time for performing bead milling can be in the range of 0.5 hours to 2 hours, particularly 0.5 hours to 1.5 hours, and more particularly 0.8 hours to 1 hour. When the time satisfies the above range, the diameter of the carbon nanotube structure can be appropriately regulated without destroying the carbon nanotube structure during the dispersion process, and a dispersed solution with a uniform composition can be prepared. The execution time of bead milling refers to the total time of using bead milling, so, for example, if bead milling is performed several times, the execution time refers to the total time required for performing several bead millings.
[0092] The above bead milling conditions are for dispersing the bundle-type single-walled carbon nanotubes at an appropriate level, and specifically exclude the case where the bundle-type single-walled carbon nanotubes are completely dispersed into single-chain single-walled carbon nanotubes. That is, the above bead milling conditions are for forming a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side in a conductive agent dispersion prepared by appropriately dispersing the bundle-type single-walled carbon nanotubes. This can be achieved only when the composition of the mixed solution and the conditions of the dispersion process (e.g., bead milling process) are strictly regulated.
[0093] The carbon nanotube structure dispersion can be formed by the above method.
[0094] (2) Formation of electrode slurry including graphene dispersion, carbon nanotube structure dispersion and electrode active material (S2)
[0095] When the graphene dispersion and the carbon nanotube structure dispersion are prepared by the above method, an electrode slurry including the dispersion and the electrode active material is formed. In this case, the above electrode active material can be used as the electrode active material.
[0096] In addition, if necessary, the electrode slurry may further include a binder and a solvent. In this case, the binder of the above embodiment can be used as a binder. The solvent may include, for example: an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol ; Polyhydroxy alcohol, such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; Ethylene glycol ether, such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; Ketone, such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; Esters, such as ethyl acetate, γ-butyrolactone and ε-propiolactone, and any one of them or a mixture of two or more thereof can be used, but the present invention is not limited thereto. The solvent may be the same as or different from the dispersion medium used in the pre-dispersion, and the solvent may preferably be N-methylpyrrolidone (NMP).
[0097] Next, the electrode slurry prepared as described above is dried to form an electrode active material layer. Specifically, the electrode active material layer can be prepared by coating the electrode slurry on an electrode collector and drying the coated electrode collector, or can be prepared by casting the electrode slurry on a separate carrier and then laminating the film separated from the carrier on the electrode collector. If necessary, an electrode active material layer can be formed by the above method, and then a rolling process can be further performed. In this case, taking into account the physical properties of the electrode finally prepared, drying and rolling can be performed under appropriate conditions, and there is no particular restriction.
[0098] Secondary battery
[0099] A secondary battery according to another embodiment of the present invention may include a negative electrode, a positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode may be the electrode of the above embodiment. Specifically, the electrode of the above embodiment may be the positive electrode of this embodiment.
[0100] The separator separates the negative electrode and the positive electrode and provides a mobile path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is generally used for secondary batteries, and in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transmission of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or a laminated structure having two or more layers thereof can be used as a separator. In addition, conventional porous nonwoven fabrics can be used, for example, nonwoven fabrics formed by high melting point glass fibers or polyethylene terephthalate fibers. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.
[0101] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.
[0102] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0103] As the nonaqueous organic solvent, for example, aprotic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfranc, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0104] Especially, in carbonate-based organic solvents, because ethylene carbonate and propylene carbonate as cyclic carbonate dissociate lithium salts well due to high dielectric constant as high viscosity organic solvent, cyclic carbonate can be preferably used.Because when above-mentioned cyclic carbonate is mixed with low viscosity, straight-chain carbonate of low dielectric constant such as dimethyl carbonate and diethyl carbonate and used in appropriate ratio, electrolyte with high conductivity can be prepared, so cyclic carbonate can be more preferably used.
[0105] As the metal salt, a lithium salt may be used, and the lithium salt is a material that is easily soluble in a non-aqueous organic solvent, wherein, as an anion of the lithium salt, for example, at least one selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0106] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, in addition to the electrolyte components, at least one additive can be further added to the electrolyte, for example, a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum chloride.
[0107] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. Since the battery module and the battery pack include secondary batteries having high capacity, high rate performance, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0108] Hereinafter, the present invention will be described in detail according to specific examples and comparative examples.
[0109] Preparation Example 1: Preparation of graphene dispersion
[0110] Chemically expanded graphene (in powder form), hydrogenated nitrile rubber (H-NBR) as a dispersant, and N-methylpyrrolidone (NMP) as a dispersion medium were mixed in a weight ratio of 3.6:1.2:95.2 to form a mixture. The mixture was added to a pin mill in which 80% was filled with beads having a diameter of 0.65 mm, dispersed, and discharged at a discharge rate of 2 kg / min. By performing this process twice, the chemically expanded graphene was completely dispersed to prepare a graphene dispersion (see Figure 3 ).
[0111] Preparation Example 2: Preparation of Carbon Nanotube Structure Dispersion
[0112] Bundle-type single-walled carbon nanotubes (specific surface area 650 m2) consisting of single-walled carbon nanotube units with an average diameter of 1.5 nm and an average length of 5 μm or more 2 / g) and polyvinylidene fluoride (PVdF, KF9700, weight average molecular weight: 880,000 g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture having a solid content of 2.4 wt%.
[0113] The bundle-type single-walled carbon nanotubes were dispersed in the solvent by stirring the mixture by a bead mill method, and thus a carbon nanotube structure dispersion was prepared. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes. The carbon nanotube structure dispersion includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are connected side by side (see Figure 2 A).
[0114] In the carbon nanotube structure dispersion, the amount of the carbon nanotube structure was 0.4 wt %, and the amount of the polyvinylidene fluoride was 2.0 wt %.
[0115] Preparation Example 3: Preparation of Carbon Nanotube Structure Dispersion
[0116] A carbon nanotube structure dispersion was prepared in the same manner as in Preparation Example 2, except that the polyvinylidene fluoride in Preparation Example 2 was replaced with hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol).
[0117] Preparation Example 4: Preparation of Carbon Black Dispersion
[0118] The specific surface area is 240m 2 / g of carbon black (in the form of secondary particles consisting of primary particles with an average diameter of 25nm) and hydrogenated nitrile rubber (weight average molecular weight: 260,000g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture with a solid content of 16.5wt%.
[0119] By stirring the mixture by a bead mill method, carbon black was dispersed in the solvent, and thus a carbon black dispersion was prepared. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes.
[0120] In the carbon black dispersion, the amount of carbon black was 15 wt % and the amount of hydrogenated nitrile rubber was 1.5 wt %.
[0121] Preparation Example 5: Preparation of single-walled carbon nanotube unit dispersion
[0122] Bundle-type single-walled carbon nanotubes (specific surface area 650 m2) consisting of single-walled carbon nanotube units with an average diameter of 1.5 nm and an average length of 5 μm or more 2 / g) and hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture with a solid content of 4.4 wt% (0.4 wt% of bundle-type single-walled carbon nanotubes, 4 wt% of hydrogenated nitrile rubber).
[0123] By stirring the mixture by a bead mill method, the bundle-type single-walled carbon nanotubes were dispersed in the solvent, and thus a conductive agent dispersion was prepared. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring for 60 minutes under the above conditions was set as 1 cycle, and a total of 4 cycles were performed (natural cooling was performed for 60 minutes between each cycle). Thus, a single-walled carbon nanotube unit dispersion was prepared (see Figure 2 B). In the dispersion, since the bundle-type single-walled carbon nanotubes are completely dispersed, the single-walled carbon nanotube units exist only as single chain units, and the above-mentioned carbon nanotube structure is not detected. In addition, in the single-walled carbon nanotube unit dispersion, the amount of the carbon nanotube structure is 0.4% by weight, and the amount of the hydrogenated nitrile rubber is 4.0% by weight.
[0124] Preparation Example 6: Preparation of Multi-walled Carbon Nanotube Unit Dispersion
[0125] The bundle-type multi-walled carbon nanotubes, hydrogenated nitrile rubber (H-NBR) as a dispersant, and N-methylpyrrolidone (NMP) as a dispersion medium were mixed in a weight ratio of 4:0.8:95.2 to form a mixture. The mixture was added to a pin mill in which 80% was filled with beads having a diameter of 0.65 mm, dispersed, and discharged at a discharge rate of 2 kg / min. By performing this process twice, the bundle-type multi-walled carbon nanotubes were completely dispersed to prepare a multi-walled carbon nanotube unit dispersion.
[0126] Examples and Comparative Examples
[0127] Example 1: Preparation of positive electrode
[0128] The graphene dispersion of Preparation Example 1, the carbon nanotube structure dispersion of Preparation Example 2, and LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2O2 (NCM622) and a binder (PVDF, KF9700) were mixed with N-methylpyrrolidone (NMP) to prepare a positive electrode slurry with a solid content of 70.4%. The positive electrode slurry was coated on a 20 μm thick aluminum (Al) film collector, dried at 130°C, and then rolled to prepare a positive electrode including a positive electrode active material layer.
[0129] 97.8 wt% LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), 1.7 wt% of a binder, 0.1 wt% of hydrogenated nitrile rubber, 0.3 wt% of graphene, and 0.1 wt% of a carbon nanotube structure were included in the positive electrode active material layer.
[0130] Reference Figure 4 It can be confirmed that in the positive electrode of Example 1, the carbon nanotube structure in the form of a rope together forms a network structure while having a long length to connect the NCM622 particles to each other. In addition, it can be confirmed that the graphene with a large surface tightly forms a conductive network while covering the carbon nanotube structure.
[0131] Example 2: Preparation of positive electrode
[0132] A positive electrode was prepared in the same manner as in Example 1, except that the carbon nanotube structure of Preparation Example 3 was used instead of the carbon nanotube structure of Preparation Example 2.
[0133] Example 3: Preparation of positive electrode
[0134] A positive electrode was prepared in the same manner as in Example 1, except that 0.2 wt % of graphene and 0.1 wt % of carbon nanotube structure were included in the final positive electrode by changing the amounts of the graphene dispersion of Preparation Example 1 and the carbon nanotube structure dispersion of Preparation Example 2 used.
[0135] Comparative Example 1: Preparation of positive electrode
[0136] A positive electrode was prepared in the same manner as in Example 1, except that 0.7 wt % of carbon black was used as a conductive agent for the positive electrode active material layer by using the carbon black dispersion of Preparation Example 4 instead of the graphene dispersion of Preparation Example 1 and the carbon nanotube structure dispersion of Preparation Example 2.
[0137] Comparative Example 2: Preparation of positive electrode
[0138] A positive electrode was prepared in the same manner as in Example 1, except that by using only the graphene dispersion of Preparation Example 1 without using the carbon nanotube structure dispersion of Preparation Example 2, 0.7 wt % of graphene was included in the positive electrode active material layer.
[0139] Comparative Example 3: Preparation of positive electrode
[0140] A positive electrode was prepared in the same manner as in Example 1, except that by using only the carbon nanotube structure dispersion of Preparation Example 2 instead of the graphene dispersion of Preparation Example 1, 0.7 wt % of the carbon nanotube structure was included in the positive electrode active material layer.
[0141] Comparative Example 4: Preparation of positive electrode
[0142] A positive electrode was prepared in the same manner as in Example 1, except that the single-walled carbon nanotube unit dispersion of Preparation Example 5 was used instead of the carbon nanotube structure dispersion of Preparation Example 2.
[0143] Comparative Example 5: Preparation of positive electrode
[0144] A positive electrode was prepared in the same manner as in Example 1, except that the multi-walled carbon nanotube unit dispersion of Preparation Example 6 was used instead of the carbon nanotube structure dispersion of Preparation Example 2.
[0145] [Table 1]
[0146]
[0147] In Example 1, Example 3 and Comparative Example 3, the average diameter of the carbon nanotube structure is 100 nm, and the average length thereof is 15.6 μm. In Example 2, the average diameter of the carbon nanotube structure is 10 nm, and the average length thereof is 8.2 μm. In Comparative Example 4, the average diameter of the single-walled carbon nanotube unit is 1.6 nm, and the average length thereof is 1.8 μm. In Comparative Example 5, the average diameter of the multi-walled carbon nanotube unit is 10.8 nm, and the average length thereof is 1.3 μm.
[0148] When the prepared positive electrode is observed by TEM, the average diameter and the average length correspond to the average value of the diameters (or lengths) of the first 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) with larger diameters (or lengths) and the last 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) with smaller diameters (or lengths).
[0149] In Examples 1, 2 and 3 and Comparative Examples 2, 4 and 5, the average length of the graphene is 4.6 μm and the average thickness thereof is 5.3 nm, and when the prepared positive electrode is observed by TEM, the average length and the average thickness correspond to the average value of the length (or thickness) of the first 100 graphenes with larger lengths (or thicknesses) and the lengths (or thicknesses) of the last 100 graphenes with smaller diameters (or lengths).
[0150] Test Example 1: Observation of the positive electrode
[0151] The positive electrodes of Example 1, Comparative Example 4 and Comparative Example 5 were observed by SEM.
[0152] Reference Figure 4 and Figure 5 In the positive electrode of Example 1, it can be confirmed that the carbon nanotube structure in the form of a rope (a form in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and bonded to each other) forms a network structure together, while having a long and thick shape to connect the NCM622 particles to each other. In addition, it can be confirmed that the graphene with a large surface tightly forms a conductive network while covering the carbon nanotube structure.
[0153] In contrast, reference Figure 6 , the fully dispersed single-chain single-walled carbon nanotube units in the positive electrode of Comparative Example 4 are mostly present on the surface of graphene, and it can be understood that their length or diameter is significantly smaller than that of the carbon nanotube structure of Example 1. In addition, referring to Figure 7 In the positive electrode of Comparative Example 5, multi-walled carbon nanotube units with extremely short lengths and aggregated together were observed on the surface of graphene. It can be understood that their lengths or diameters are significantly smaller than those of the carbon nanotube structure of Example 1.
[0154] Test Example 2: Evaluation of Powder Resistance of Positive Electrode Slurry
[0155] The powder resistance of the positive electrode slurry formed in the preparation of the positive electrodes of Examples 1 to 3 and Comparative Examples 1 to 5 was evaluated by the following method.
[0156] The positive electrode slurry was vacuum dried at a temperature of 130° C. for 3 hours and then ground to prepare a powder. Thereafter, the powder was prepared into pellets using a Loresta GP instrument purchased from Mitsubishi Chem Analytic Co., Ltd. at 25° C. under a load of 9.8 MPa and a relative humidity of 50%. Thereafter, the powder resistance was measured by a 4-probe method, and the results are shown in Table 2.
[0157] Test Example 3: Battery Life Characteristics Evaluation
[0158] Batteries were prepared using the positive electrodes of Examples 1 to 3 and Comparative Examples 1 to 5 as follows.
[0159] Artificial graphite as a negative electrode active material, carbon black as a negative electrode conductive agent, styrene butadiene rubber (SBR) as a negative electrode binder, and carboxymethyl cellulose (CMC) were mixed in distilled water at a weight ratio of 96.1:0.5:2.3:1.1 to prepare a negative electrode slurry. A 20 μm thick negative electrode collector (Cu) was coated with the prepared slurry so that the loading amount was 10 mg / cm 2 , and dried. Thereafter, the negative electrode current collector on which the negative electrode slurry was arranged was rolled by a rolling method so that the total thickness of the negative electrode slurry and the negative electrode current collector was 80 μm. Thereafter, the negative electrode slurry and the negative electrode current collector were dried at 110° C. for 6 hours to prepare a negative electrode.
[0160] Afterwards, after preparing a single cell by assembling the above-prepared negative electrode and the above-prepared positive electrode with a 15μm thick polyethylene-based separator arranged therebetween, an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1 / 2 (volume ratio)) and lithium hexafluorophosphate (1M LiPF6) are injected into the single cell to prepare a lithium secondary battery.
[0161] Charging and discharging of each lithium secondary battery was performed under the following conditions.
[0162] Each lithium secondary battery was set to charge / discharge at 0.33C / 0.33C in a voltage range of 4.25V to 2.8V at 45°C as one cycle, and a total of 100 cycles were performed. Thereafter, the discharge capacity (capacity retention rate) after 100 cycles was evaluated based on the discharge capacity after 1 cycle being 100%, and is shown in Table 2.
[0163] [Table 2]
[0164]
[0165]
[0166] The following content corresponds to the original claims in the parent application and is now incorporated herein as part of the specification:
[0167] 1. An electrode comprising an electrode active material layer,
[0168] The electrode active material layer comprises an electrode active material and a conductive agent,
[0169] The conductive agent comprises:
[0170] Graphene; and
[0171] A carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and
[0172] The carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.
[0173] 2 . The electrode according to claim 1 , wherein a weight ratio of the graphene to the carbon nanotube structure is in a range of 100:1 to 100:200.
[0174] 3. The electrode according to item 1, wherein the graphene is included in the electrode active material layer in an amount of 0.01 wt % to 1.0 wt %.
[0175] 4. The electrode according to item 1, wherein the carbon nanotube structures are interconnected in the electrode to form a network structure.
[0176] 5. The electrode according to item 1, wherein the single-walled carbon nanotube units are arranged side by side and combined in the carbon nanotube structure.
[0177] 6. The electrode according to item 1, wherein the average length of the carbon nanotube structure is 1 μm to 500 μm.
[0178] 7. The electrode according to item 1, wherein the average length of the carbon nanotube structure is 10 μm to 70 μm.
[0179] 8. The electrode according to item 1, wherein the average diameter of the carbon nanotube structure is 2 nm to 200 nm.
[0180] 9. An electrode according to item 1, wherein the average diameter of the carbon nanotube structure is 50 nm to 120 nm.
[0181] 10. The electrode according to item 1, wherein in the carbon nanotube structure, the average diameter of the single-walled carbon nanotube units is 0.5 nm to 5 nm.
[0182] 11. The electrode according to item 1, wherein the average length of the graphene is 0.1 μm to 100 μm.
[0183] 12. An electrode according to item 1, wherein the average thickness of the graphene is 0.3 nm to 300 nm.
[0184] 13. The electrode according to item 1, wherein the carbon nanotube structure is a carbon nanotube structure in which 50 to 4,000 single-walled carbon nanotube units are bonded to each other.
[0185] 14. An electrode according to item 1, wherein the electrode is a positive electrode.
[0186] 15. A secondary battery comprising the electrode according to any one of items 1 to 14.
Claims
1. An electrode comprising an electrode active material layer, The electrode active material layer comprises an electrode active material and a conductive agent, The conductive agent comprises: Graphene with an average length of 0.1 μm to 100 μm; and A carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and bonded to each other, wherein the average length of the carbon nanotube structure is 1 μm to 500 μm, and The carbon nanotube structures are interconnected in the electrode to form a network structure. 2 . The electrode according to claim 1 , wherein a weight ratio of the graphene to the carbon nanotube structure is in a range of 100:1 to 100:
200. 3 . The electrode according to claim 1 , wherein the graphene is included in the electrode active material layer in an amount of 0.01 wt % to 1.0 wt %. 4 . The electrode according to claim 1 , wherein the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %. 5 . The electrode according to claim 1 , wherein the carbon nanotube structure has an average length of 5 μm to 100 μm. The electrode according to claim 1 , wherein the carbon nanotube structure has an average length of 10 μm to 70 μm. The electrode according to claim 1 , wherein the average diameter of the carbon nanotube structure is 2 nm to 200 nm. The electrode according to claim 1 , wherein the carbon nanotube structure has an average diameter of 50 nm to 120 nm. 9 . The electrode according to claim 1 , wherein in the carbon nanotube structure, an average diameter of the single-walled carbon nanotube unit is 0.5 nm to 5 nm. 10 . The electrode according to claim 1 , wherein an average length of the graphene is 0.1 μm to 10 μm. The electrode according to claim 1 , wherein the graphene has an average thickness of 0.3 nm to 300 nm. 12 . The electrode according to claim 1 , wherein the carbon nanotube structure is a carbon nanotube structure in which 50 to 4,000 single-walled carbon nanotube units are bonded to each other.
13. The electrode according to claim 1, wherein the electrode is a positive electrode. 14 . A secondary battery comprising the electrode according to claim 1 .
Citation Information
Patent Citations
Distribution system and method for lending clothes
KR1020190122965A